Knowledge Sharing, Individualism, Collectivism, and Organizational Innovative Behaviour in Public Health Organizations - Khawaja Asif Tasneem; Saba Feroz Qureshi (European Scientific Journal, ESJ, 2022)
This paper focuses on investigating the more innovative employees, i.e., individualists or collectivists, in the public sector when it comes to knowledge sharing and organizational culture. The study adopted quantitative research technique and data was collected through an online survey. A field study was conducted and data was obtained from 480 employees working in Pakistan's two major public health institutions so as to test the study's hypotheses. A hierarchical linear regression model was used to test the hypotheses. The results show that there is a significant positive influence of organizational-based knowledge sharing, individual-based knowledge sharing, collectivism, and individualism on organizational innovative behaviour in the organizations. This study also found a significant positive impact of collectivism and individualism as moderators on organizational innovative behaviours. The study further concluded that collectivism has a higher positive impact on organizational innovative behaviour in comparison to individualism.